Information Model for Global Seaborne Shipping from 2010 to 2020 - Vidučić, Vinko; Bukljaš Skočibušić, Mihaela; Žanić Mikuličić, Jelena (Transactions on Maritime Science, 2017)
The research has focused on the development of the global seaborne shipping market from 2010 to 2020. The analysis and assessment of the relevant variables of the model and the resulting growth rates have been aimed at a scientific formulation of the research findings and have been used to describe the most important theoretical principles governing the global seaborne shipping market over the defined period of time. The basic hypothesis has been confirmed through the direct growth rates of the selected model variables. In this way a scientific confirmation of the hypothesis has been provided: "On the basis of scientific insights into the global seaborne shipping market, it is possible to suggest a new information model for the development of the global seaborne shipping market for the period 2010 – 2020.